Mastering digital audio production : - Truesdell, Cliff (Wiley Publishing, 2007)
This comprehensive guide shows you how to integrate a variety of production tools for the Mac OS X platform into all stages of audio production so that you can create and produce music. From single applications to complete suites, you'll discover the software toolsets that are best for you and then discover how to incorporate them into a coherent workflow. Featuring best practices, real-world examples, and interviews with audio professionals, this book pulls together all the programs and tasks you need.